PENGARUH KEPEMIMPINAN, MOTIVASI KERJA, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCACATAN SIPIL KAB. KERINCI - Fitrina Afrianti (LPPM - STIE SAKTI ALAM KERINCI, 2019)
Public services are linked to leadership, motivation, compensation, and discipline are becoming one of humans resources concern today. This study aims to uncover relationship between leadership, motivation, compensation, and discipline on Civil Registry Kab. Kerinci. This study uses quantitative method, with exogenous variables, namely leadership variable (X1), motivation (X2), compensation (X3), discipline as intervening variable (X4) and endogenous variables, namely employee performance (Y). The data collection technique is propotional stratified random sampling. And the data analysis used is path analysis that devided into 2 paths, those are: sub structure 1 and sub structure 2. Data was collected through questionnares that have been tested for reability and validity. The results of this study show that there are relation leadership on employee performance is 3,7%, motivation on perfomance is 11,8%, compencation on performance is 4,2%, and relation between discipline on performance is 2,4%.